Consumer Expectations towards Clinic Services. - Anne, Tay Pek See (Universiti Malaysia Sarawak (UNIMAS), 2005)
This research aims to study of Consumer expectation towards clinic services in identifying the important dimensions of quality service that are expected by the consumer towards their clinic services in Kuching area. This paper attempt to determine the expectation through the internationally used market research technique called SERVQUAL. It analyzes the five SERVQUAL dimensions; tangibility, reliability, responsiveness, assurance and empathy which are influence consumers' expectation towards clinic services. An analysis covering 200 of respondents who have been experience with clinic services to identify their expectation towards clinic services. The result of the Pearson Correlation had shown that the five SERVQUAL dimensions having the positive relationship with the consumer expectation. Thus, the regression analysis is to determine the relative importance dimension which is expected by the consumers. Among the SERVQUAL dimensions, reliability as a dominant contributed to the consumer clinic services expectation. Reliability in services is defined as the ability to perform the promised service dependably and accurately. It means that the clinic should perform the service right on the first time and also means that honors all of its promises. This research found that consumers are expected to have 64.3 percent of reliability dimension in the clinic services. Customers indicated that their clinic services most serious shortcoming was lack of reliability. These results seem to indicate that the most important service quality dimension for consumers is reliability.